Local ecological knowledge (LEK) reveals the drivers and barriers for sustainable conservation of protected forest biodiversity - Tinotenda Rosemary Kembo; Beaven Utete (Sustainable Environment)
Understanding the key drivers and barriers to sustainable conservation of protected and unprotected forests, heavily utilised by humans and wildlife, is essential in sustainable forest management and law enforcement. This study aimed to: i) evaluate fringe community perceptions towards forest biodiversity sustainability across villages; ii) establish the key drivers and barriers of biodiversity conservation, and iii) develop an integrated conservation framework for the Gwaai Forest in Zimbabwe. Data were collected from 143 respondents using questionnaires, key informant interviews and direct observations. Locals, simultaneously, preferred and exerted negative pressure on clusterleaf Terminalia sericea and African teak Baikea plurijuga for carving, roofing and furniture making increasing the distance travelled to collect forest products. Human population increase, poaching, veld fires and overexploitation were the key barriers whereas tangible and intangible benefits for local people and improved management systems were the key drivers of sustainable conservation. Gwaai Forest access and utilisation is heavily regulated by the forest authorities whose policies are not human centred but rather aimed at maintaining the resilience and stability of the forest. There is a need to explore suitable alternative livelihoods such as farming of drought resistant small grains less dependent on the Gwaai Forest ecosystem services to reduce pressure on tree species and other natural resources. An in-depth understanding of the ecological, economic, and social factors that influence forest resilience is necessary for planning and managing Gwaai Forest operations efficiently.